Influence of exogenous abscisic acid on morpho-physiological and yield of maize (Zea mays L.) under drought stress - Ramya, S; Arulbalachandran, D; Ramachandran, M (Plant Science Today, 2022)
Abscisic acid (ABA) is naturally occurring plant hormone, its also known stress hormone, that act the plant responses to abiotic stresses, especially drought. Maize production losses due to drought prominently affect economics and livelihoods of millions of peoples. The current investigation the role of ABA in drought stress tolerance of maize. The influence of drought stress and foliar spray of abscisic acid diffent concentration (25, 50 ,75 and 100 µM) were analysed on morphological, physiological, and biochemical parameters. The present results revealed a most effective to increased after drought stress imposed with 75 µM ABA treated plants. Exogenous abscisic acid acts as a scavenger of ROS for mitigating the injury on cell membranes under drought were observed in the opening of stomata. Histochemical detection of more accumulation ROS (H2O2 and O2• –) was detected in drought stress shoot compared to other ABA treated and respective control. Fourier Infrared Spectroscopic (IR) study, ABA treated leaves indicated the presence of different functional groups. This study shows that can provide vital insights into maize leaves drought responses and could be beneficial in identifying novel drought tolerance characters. Drought and exogenous abscisic acid treatment increased the endogenous abscisic acid level, specifically at 75 µM concentration. The exogenous abscisic acid application effectively ameliorates the adverse effect of drought stress to improve the drought resistance. In concluded, the level of 75 µM concentration ABA was better growth charaterstics, biochmeical alterations and yiled under drought stress.